THE EFFECT OF LEADERSHIP, INTERNAL CONTROL SYSTEM, AND ORGANIZATIONAL COMMITMENT ON ACCOUNTABILITY OF VILLAGE FINANCIAL MANAGEMENT - Savitri, Enni; Andreas, Andreas; Diyanto, Volta; Gumanti, Tatang Ary (Universitas Brawijaya, Indonesia, 2020)
This study aims to analyze the influence of leadership, internal control system, and organizational commitment on the accountability of village fund management in Kampar and Siak Districts. A total of 164 financial management officials from 218 villages in 15 subdistricts in Kampar and Siak Regencies were selected as the respondents. The villages are located in coastal areas and watersheds. The data were obtained by distributing questionnaires distributed directly to the respondents. The data were analyzed using multiple linear regression. The results show that leadership, internal control system, organizational commitment affect significantly the accountability of village fund management. Future research on the same issue may examine both internal control and external control system.